PTH-009 Ercp Under Propofol: Do Patients Prefer It?. (9th June 2014) - Steed, H; Potter, M; Leithead, J; Lau, K; Glass, R; Hebbar, S; Durkin, D; Deakin, M; Green, J
Abstract : Introduction: Endoscopic retrograde cholangiopancreatography (ERCP) is an invasive procedure involving heavy sedation. Use of propofol as sedation in ERCP has been demonstrated to be safe, but is it preferred by patients? Methods: A prospectively collected dataset of patient satisfaction questionnaires post ERCP, using a Likehart scale. Patients excluded were those who declined to do so, those unable to consent for themselves. After 30 days patients were contacted by an ERCP-trained nurse to discuss any problems and complications arising in that time. Results: 128 questionnaires have been completed and followed up at 30-days. 26 had the procedure under propofol +/- midazolam and fentanyl (administered by an anaesthetist) and 102 under a combination of midazolam and fentanyl as per standard unit practice administered by the ERCPist. 30-day FU: 93 of 103 agreed to contact, 16 of whom were uncontactable (based on 2–3 separate attempts to call them on the number provided), 4 of 23 uncontactable from propofol group. 5 propofol patients reported problems in the 30 day follow up (2 were serious), compared to 24 of the sedation group (4 of which were serious). There was no difference in overall satisfaction between the groups, the propofol group reported less discomfort during the procedure (p < 0.001), less wretching (p = 0.015) and were more willing to have the procedure repeated (p = 0.051). Using a score of 1 and 2 for satisfied and anyone reporting a score of 3–7 as less or not satisfied, the factors associated with less satisaction were discomfort during the procedure (=0.006), overall discomfort (p = 0.001), overall rating of experience and unwillingness to repeat the procedure (p < 0.001). After adjusting for age, gender and number of interventions there was no association between propofol use and non satisfaction (adjusted OR 1.12 (95% CI: 0.28–4.45), p = 0.868). Conclusion: Patients do prefer ERCP under propofol, but not by much. They get less discomfort (where 0 was a scale of no discomfort and 7 of extreme pain) and therefore are more willing to have the procedure done again. Interestingly propofol procedures are not taking longer than normally-sedated procedures and there are not higher numbers of therapeutic interventions. This may reflect the current bias in selecting a propofol list for a patient or form part of the learning curve of finding the role of propofol-ERCP in the therapeutic strategy. Further data collection is required to see if ERCP under propofol reduces the number of repeat procedures and therefore can justify itself as cost-effective. Disclosure of Interest: None Declared.